2004
DOI: 10.1366/0003702041655458
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Analysis for Inspecting Carbonation of Concrete Using a TEA CO2 Laser-Induced Plasma

Abstract: It has been demonstrated that a spectrochemical analysis of carbon using the laser plasma method can be successfully applied to inspect the carbonation of concrete by detecting carbon produced in aged concrete by a chemical reaction of Ca(OH)2 with CO2 gas in environmental air, turning into CaCO3, which induces degradation of the quality of building concrete. A comparative study has been made using a TEA CO2 laser (500-1000 mJ) and a Q-switched Nd-YAG laser (50-200 mJ) to search for the optimum conditions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…In our previous publications, which mainly used a single laser in a low pressure surrounding gas, we confirmed that no self-absorption is observed in the emission lines 26 40 . We also reported in another publication that the self-absorption effect can be significantly suppressed by applying a double pulse orthogonal configuration in atmospheric He gas.…”
Section: Introductionsupporting
confidence: 85%
“…In our previous publications, which mainly used a single laser in a low pressure surrounding gas, we confirmed that no self-absorption is observed in the emission lines 26 40 . We also reported in another publication that the self-absorption effect can be significantly suppressed by applying a double pulse orthogonal configuration in atmospheric He gas.…”
Section: Introductionsupporting
confidence: 85%
“…The experimental set up used in this work is similar to that used in our previous work except for the laser source. 1 In this experiment, a Nd:YAG laser (Quanta Ray, LAB SERIES, 400 mJ, 5 ns) was operated in the Q-switched mode at a 10 Hz repetition rate with the laser output energy fixed at 50 mJ. The laser beam was focused by a lens (f ¼ 100 mm) through a quartz window onto the sample surface.…”
Section: Methodsmentioning
confidence: 99%
“…From this point of view, we reported on a new technique for inspecting the carbonation of concrete, which induces its degradation, in terms of TEA CO 2 laser-induced plasma spectroscopy, based on detecting the emission line of C(I) 247.9 nm. 1 On the other hand, concrete hardness (compressive strength) inspection is absolutely important. It is assumed that a laser-induced plasma (LIP) technique could also be used to determine hardness because the plasma characteristics are inherently related to the hardness of the target.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental arrangement used in this study is almost similar to that used in our previous work. 15 The TEA CO 2 laser used in this work is a Shibuya SQ-2000 laser, which was developed and constructed by the Shibuya Company for laser marking. The laser light from the TEA CO 2 laser (3 J, 10.6 m, 200 ns), was focused through a ZnSe window onto a sample using a ZnSe lens with a focal length of 100 mm, after the laser energy was reduced to 500 mJ by inserting an aperture in front of the focusing lens.…”
Section: Methodsmentioning
confidence: 99%